ILAE definition of the Idiopathic Generalized Epilepsy Syndromes: Position statement by the ILAE Task Force on Nosology and Definitions. Issue 6 (3rd May 2022) - Hirsch, Edouard; French, Jacqueline; Scheffer, Ingrid E.; Bogacz, Alicia; Alsaadi, Taoufik; Sperling, Michael R.; Abdulla, Fatema; Zuberi, Sameer M.; Trinka, Eugen; Specchio, Nicola; Somerville, Ernest; Samia, Pauline; et al.
Abstract: In 2017, the International League Against Epilepsy (ILAE) Classification of Epilepsies described the "genetic generalized epilepsies" (GGEs), which contained the "idiopathic generalized epilepsies" (IGEs). The goal of this paper is to delineate the four syndromes comprising the IGEs, namely childhood absence epilepsy, juvenile absence epilepsy, juvenile myoclonic epilepsy, and epilepsy with generalized tonic–clonic seizures alone. We provide updated diagnostic criteria for these IGE syndromes determined by the expert consensus opinion of the ILAE's Task Force on Nosology and Definitions (2017–2021) and international external experts outside our Task Force. We incorporate current knowledge from recent advances in genetic, imaging, and electroencephalographic studies, together with current terminology and classification of seizures and epilepsies. Patients that do not fulfill criteria for one of these syndromes, but that have one, or a combination, of the following generalized seizure types: absence, myoclonic, tonic‐clonic and myoclonic‐tonic‐clonic seizures, with 2.5–5.5 Hz generalized spike‐wave should be classified as having GGE. Recognizing these four IGE syndromes as a special grouping among the GGEs is helpful, as they carry prognostic and therapeutic implications.